Cockroach-inspired structure for low-frequency vibration isolation. (15th May 2022) - Ling, Peng; Miao, Lunlun; Zhang, Wenming; Wu, Chuanyu; Yan, Bo
Abstract: Insects bear huge external loads without injury, for example, cockroaches can withstand forces up to 900 times body weight owing to the shape-changing ability of their jointed exoskeletons and striated muscles, which can absorb huge energy and dissipate by the damping of body-friction. This paper presents a cockroach-inspired structure (CIS) by mimicking the body topology of cockroaches for low-frequency vibration isolation. The exoskeletons, which provide the low-frequency characteristic, are mimicked by a diamond-shape chamber. The striated muscles providing the restoring force are mimicked by springs, and the front legs are mimicked by rods and sliders. The diamond-shape chamber contributes to nonlinear stiffness and the sliders lead to nonlinear damping and inertia effects. The theoretical model was established and the comprehensive parameter studies and optimization efforts were carried out to verify the vibration isolation performance of CIS. The results demonstrate that the nonlinear properties of CIS can dramatically reduce the resonant frequency and peak transmissibility. The spring assembly direction influences the vibration isolation performance. CIS exhibits an anti-resonance phenomenon under a larger inertia. This study creatively provides a type of insect-inspired structures for high-stability and cost-effectiveness low-frequency vibration isolation.